Cambodia Economic Update, April 2016 : Improving Macroeconomic and Financial Resilience - World Bank Group (World Bank, Washington, DC, 2016)
While remaining robust, growth in 2015 eased slightly to 7.0 percent, slightly below the 7.1 percent achieved in 2014. The performance of the garment sector improved in 2015, while signs of economic moderation and weakness persisted in the tourism and agriculture sectors, respectively. Cambodia’s real growth is projected to remain healthy at 6.9 percent in 2016, driven partly by a significant increase in government spending. Strong garment exports should help to offset a slowdown in agriculture, while the construction sector is expected to continue to remain an engine of growth. Downside risks to this outlook include potential renewed labor issues, continued appreciation of the United States (U.S.) dollar, slower economic recovery in Europe, and spillovers from a slowdown in the Chinese economy. The downward trend in poverty is expected to continue over the next few years, albeit at a slower pace, given the context of sluggish agriculture growth.